Potential of Cricket (Acheta domesticus) Flour as a Lean Meat Replacer in the Development of Beef Patties - Carlos Pasqualin Cavalheiro; Claudia Ruiz-Capillas; Ana M. Herrero; Tatiana Pintado; Camila Cristina Avelar de Sousa; Juliana Sant’Ana Falcão Leite; Maurício Costa Alves da Silva (Foods, 2024)
This study examined the incorporation of cricket (Acheta domesticus) flour (CF) (0, control; 5.0%, CF5.0; 7.5%, CF7.5; and 10.0%, CF10.0) as a lean meat replacer in beef patties and its impact on composition, microbiological, sensory, and technological properties, as well as its influence on the cooking process. The inclusion of CF led to beef patties with significantly higher protein levels than the control group. Additionally, an elevation in total viable (TVC) and lactic acid bacteria (LAB) counts was observed. However, Enterobacteriaceae counts remained at safe levels. CF5.0 demonstrated similar sensory scores and purchase intention to the control treatment. CF7.5 and CF10.0 showed comparable sensory scores to the control except for texture attributes. The inclusion of CF significantly reduced cooking loss and diameter reduction values. Beef patties with CF were notably firmer and had a browner color than the control. In general, the cooking process impacted the technological properties similarly in both the control and beef patties with CF. In all cooked samples, no significant differences in pH, redness (a*), or texture were observed. This study demonstrated that incorporating up to 5.0% CF into beef patties is optimal in terms of composition, technological, sensorial, and cooking properties.